Resilience : the science of mastering life's greatest challenges - Southwick, Steven M.; Charney, Dennis S. (Cambridge : Cambridge University Press, 2018)
Most of us at some point in our lives will be struck by major traumas such as the sudden death of a loved one, a debilitating disease, assault, or a natural disaster. Resilience refers to the ability to'bounce back' after encountering difficulty. This book provides a guide to building emotional, mental and physical resilience by presenting ten factors to help anyone become more resilient to life's challenges. Specific resilience factors such as facing fear, optimism, and social support are described through the experiences and personal reflections of highly resilient survivors. These survivors also describe real-life methods for practicing and benefiting from the resilience factors. As resilience is the complex product of genetic, psychological, biological, social, and spiritual factors, the authors investigate resilience from multiple scientific perspectives. They synthesize the latest literature on the topic, describe their own research on resilience, and quote from their interviews with highly resilient people.
What is resilience? -- Optimism: belief in a brighter future -- Facing fear: an adaptive response -- Moral compass, ethics, and altruism: doing what is right -- Religion and spirituality: drawing on faith -- Social support: learning the tap code -- Role models: providing the road map -- Training: physical fitness and strengthening -- Brain fitness: challenge your mind and heart -- Cognitive and emotional flexibility -- Meaning, purpose, and growth -- The practice of resilience.
Title from publisher's bibliographic system (viewed on 24 Apr 2018).
Keywords: Resilience (Personality trait); Adaptability (Psychology)